THE EFFECT OF VARIOUS MEDIA SCAFFOLDING ON INCREASING UNDERSTANDING OF STUDENTS’ GEOMETRY CONCEPTS - Sutiarso, Sugeng; Coesamin, Coesamin; Nurhanurawati, Nurhanurawati (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2018)
This study is a quasi-experimental research with pretest-posttest control group design, which aims to determine (1) the tendency of students in using various media scaffolding based on gender, and (2) effect of media scaffolding on increasing understanding of students’ geometry concepts. Media scaffolding used this study is chart, props, and visual. The population was the fifth grade students of State Elementary School I Gunung Terang (total 40 students), Bandar Lampung, Indonesia of the academic year 2015-2016. The sample was total sampling, respectively 20 students in the experimental class (with media scaffolding) and control class (without media scaffolding). Data were collected through observation, interview and test. Analysis of the observation and interviews data with descriptive statistics (percentage). and the test data was analyzed by (a) measuring the level of effectiveness on increasing understanding of students’ geometry concepts with formula of Hake’s Normalized Gain (g) and its interpretation, and (b) examine of hypotesis on level of effectiveness with t-test. The results of research showed that (1) the tendency of male students using the media scaffolding props, and female students using scaffolding media chart, and (2) effect of media scaffolding on increasing understanding of students’ geometry concepts is effective enough.DOI: http://dx.doi.org/10.22342/jme.9.1.4291.95-102